A confirmatory factor analysis of the Mandarin-Chinese version of the Barrett-Lennard Relationship Inventory. - Liao, Faith; Murphy, David; Barrett-Lennard, Godfrey (Taylor & Francis (Routledge), 2018)
The aim of this study was to translate and provide an initial validation for a full Mandarin-Chinese version of the Barrett-Lennard Relationship Inventory (B-L RI:MC) to include forms Other toward Self-64 (OS-64) and Other toward Self-40 (OS-40) for use in the Mandarin-Chinese research and clinical contexts. B-L RI:MC OS-64 was translated by a bilingual panel and subsequently administered to 658 Mandarin-speaking Taiwanese respondents online using an age-stratified random sampling strategy. Through both the factor analytic strategy of principle component analysis (PCA) and confirmatory factor analysis (CFA), the reliability and construct validity were investigated. The final results support the original four subscale dimensionality of the inventory. B-L RI:MC OS-64 showed Cronbach’s alpha was .96 and KMO = .97. PCA using Varimax rotation yielded a four-factor model supporting the sub-scales: level of regard, empathic understanding, unconditionality of regard and congruence, which explained 49.911% squared loading of the total variance. B-L RI:MC OS-64 and OS-40 were supported by the structures in CFA, which displayed NFI = .95 and .95, CFI = .97 and .96, IFI = .97 and .96, and RMSEA = .092 and .091, indicating a promising construct validity. In conclusion B-L RI:MC OS-64 and OS-40 versions can be considered appropriate for measuring the Rogerian therapeutic relationship conditions within a Mandarin speaking community.